KEBIJAKAN MENTERI AGAMA A. MUKTI ALI TERHADAP KEMAJUAN PENDIDIKAN ISLAM DI INDONESIA - M. Yusuf Aminuddin (LPPM Institut Agama Islam Al-Hikmah Tuban, 2015)
Religious Affairs policy is important because at the moment the new order that the Indonesian people are still in the fight for the dynamics of community life state and nation toward a more settled. This maturation process, is considered significant because the foundation in developing the life of the nation. So the role of the Department of Religion large also need to be assessed because leads to the development of Islamic education in the future. To be more focused, then limited to the figure A. Mukti Ali being very influential in Indonesia today. How Policy Minister of Religion A. Mukti Ali in the field of Islamic education? And How to Influence Policy Department of Religion at the time Minister of Religion A. Mukti Ali of the Islamic Education in Indonesia? In the world of Islamic education, Policy Department of Religion at the time A. Mukti Ali became minister of religion is the implementation of a new curriculum in Islamic educational institutions with a share of 70% general subjects and 30% of subjects of Religion. This resulted in a diploma of Islamic educational institutions have the same role with the diploma of general education institutions. As well as graduates of the schools can continue to the public school level or above. Thus, the impact of the policy of the Department of Religion is still felt to this day.